Sustainable asphalt mixes manufactured with reclaimed asphalt and modified-lignin-stabilized bitumen emulsions. (10th June 2018) - Yuliestyan, A.; Gabet, T.; Marsac, P.; García-Morales, M.; Partal, P.
Graphical abstract: Highlights: 100% asphalt reclaimed by lignin-stabilized bitumen emulsion at reduced temperature. Cationic lignin in the emulsion aqueous phase promotes hydrophobic surface coating. Higher addition of soft bitumen emulsion for lower mixing-compaction temperatures. A semi quantitative approach is proposed for estimating emulsion addition. Abstract: This work aims to develop asphalt mixes with 100% reclaimed asphalt pavements (RAP) as source of aggregates and bitumen emulsions stabilized by amine-functionalized lignin. To that end, reduced-temperature asphalt technologies between 80 and 130 °C were assessed. Previously, processing parameters of emulsions were evaluated by droplet size distribution and rheology measurements. Furthermore, a study combining Pendant drop and Sessile drop (on a prototype polyethylene surface) tests showed that emulsion aqueous phase containing modified lignin would be able to wet the hydrophobic surface of RAP. Manufactured asphalt mixes were characterized according to French design method for hot mixes, including gyratory compaction, rutting resistance, complex modulus and fatigue resistance tests. The results obtained showed that reduced-temperature asphalt mixes could be successfully prepared to meet French design requirements, which would further minimize impact to environment. However, mix design has required a semi-quantitative approach for estimating 'active' RAP binder content, by balancing the manufacturing temperature and the fresh bitumen required.